2016
DOI: 10.1097/md.0000000000002718
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Hepatic Steatosis in Living Liver Donors via Noninvasive Methods

Abstract: Hepatic steatosis assessment is of paramount importance for living liver donor selection because significant hepatic steatosis can affect the postoperative outcome of recipients and the safety of the donor. The validity of various noninvasive imaging methods to assess hepatic steatosis remains controversial. The purpose of our study is to investigate the association between noninvasive imaging methods and pathology to detect steatosis in living liver donors and to propose a prediction model for hepatic steatos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 33 publications
(45 reference statements)
0
21
0
Order By: Relevance
“…Third, NAFLD was measured by ultrasound after exclusion of secondary causes for fatty liver. Although the accuracy of ultrasound for establishing the presence of fatty liver is high, it is subject to measurement error 6 , 39 . Similarly, we used eGFR as an outcome, which has inherent limitations derived from using creatinine as a filtration marker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, NAFLD was measured by ultrasound after exclusion of secondary causes for fatty liver. Although the accuracy of ultrasound for establishing the presence of fatty liver is high, it is subject to measurement error 6 , 39 . Similarly, we used eGFR as an outcome, which has inherent limitations derived from using creatinine as a filtration marker.…”
Section: Discussionmentioning
confidence: 99%
“…Nonalcoholic fatty liver disease (NAFLD), characterized by excessive hepatic fat accumulation without significant alcohol intake, use of medications causing fatty liver, or other traditional causes of fatty liver, is the most common cause of chronic liver disease worldwide, especially in developed countries 5 , 6 . The global prevalence of NAFLD was estimated at 25.2% 7 .…”
Section: Introductionmentioning
confidence: 99%
“…We were unable to support that the effect of PNPLA3 is mechanistically related to hepatic steatosis. We measured hepatic steatosis using CT L−S , a method widely validated in the field of living-donor liver transplantation18 and in the general population,19 and found that it did not correlate with the primary outcome nor with any other genetic ( PNPLA3, TM6SF2, MBOAT7 ) or phenotypic (BMI, diabetes) parameters. We speculate that in the setting of advanced cirrhosis, liver density is overwhelmingly increased relative to hepatic steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…As NAFLD increases prevalence, the transplant community will see more NAFLD among both living donors as well. A reliable assessment of hepatic steatosis is of paramount importance for living donor selection as significant steatosis can impact the postoperative outcomes of recipients and safety of the donor[ 33 ]. Because of these challenges, the focus could be on developing and establishing a standardized protocol for the monitoring of blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%